Kosa Kata dan Gaya Bahasa dalam Novel Para Priyayi Karya Umar Kayam (Kajian Stilistika) - Rohmah, Naili Nur; Suyoto, Suyoto (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
Indonesia is a country that has a variety of cultures, not least the culture that is spread on the island of Java. Javanese people's thoughts include dances, ancient texts, Javanese script, folklore, kidung, geguritan and many more. Novel is a type of Javanese literary work in the form of prose. The story in the novel is the result of the work of imagination that discusses the problems of a person's life or various characters. The story in the novel begins with the emergence of problems experienced by the character and ends with solving the problem. In a novel, of course, there are several elements, both intrinsic and extrinsic. And in this study, the author will analyze some Javanese vocabulary and the language style in the novel Para Priyayi by Umar Kayam. Style of language can also be called figure of speech is the use of the wealth of language, the use of a certain variety to obtain certain effects that can make a literary work look alive, the overall language characteristics of a group of literary writers and the distinctive way of conveying thoughts and feelings, both orally and in writing.Â